2021
DOI: 10.18400/tekderg.561956
|View full text |Cite
|
Sign up to set email alerts
|

Metaheuristics-based Pre-Design Guide for Cantilever Retaining Walls

Abstract: A pre-design guide for cantilever retaining walls and a detail parametric study of such walls is presented here. Mathematical models based on statistical methods were improved for calculating safety factors of sliding, overturning, and slope stability of those walls. The harmony search algorithm (HSA)-a metaheuristic method-was employed to realize reasonable results of the pre-design guide from all distinct cases. Through the design algorithm, the optimal design was determined for varied soil types differently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
(15 reference statements)
1
8
0
1
Order By: Relevance
“…There is a good conformity between the experimental and the predicted results: qu, predicted=0.987qu, experimental. These results are confirmed with other researchers for the feasibility and robustness of the Taguchi method [37,38] and desirability function approach [31,39]. q 0.5 = -33.7 + 9.51C + 5.90F -0.315A + 57.6(w/b) -0.911wn + 0.124P -0.583CF -7.1C(w/b) + 0.0014CP -4.96F(w/b) + 0.0219FP + 0.560CF(w/b) -0.00151CFP (6)…”
Section: Unconfined Compression Strength (Ucs) Testsupporting
confidence: 91%
“…There is a good conformity between the experimental and the predicted results: qu, predicted=0.987qu, experimental. These results are confirmed with other researchers for the feasibility and robustness of the Taguchi method [37,38] and desirability function approach [31,39]. q 0.5 = -33.7 + 9.51C + 5.90F -0.315A + 57.6(w/b) -0.911wn + 0.124P -0.583CF -7.1C(w/b) + 0.0014CP -4.96F(w/b) + 0.0219FP + 0.560CF(w/b) -0.00151CFP (6)…”
Section: Unconfined Compression Strength (Ucs) Testsupporting
confidence: 91%
“…is value can be then set as objective to be optimized. e multiobjective optimization is still a developing concept and has been applied by Purohit [21], Kaveh et al [47], Khajehzadeh et al [49], Rahbari [23], Rahbari et al [64], Kalateh-Ahani and Sarani [68], Kayabekir et al [75], Ravichandran et al [84], Uray et al [92], Dodigović et al [94], and Tutus ¸et al [95]. e study of Kayabekir et al [75] has also attempted to vary the cost of concrete and steel to study their effects on optimization with respect to economical and sustainable design.…”
Section: Objective Functionmentioning
confidence: 99%
“…In the study, which is conducted shape optimization design by employing Taguchi method hybrid version with the HSA, more optimum design variable values have been acquired regardless of the investigating for optimum values of the HSA parameters [32]. In the study which used statistical mathematical models improved by considering the Taguchi method employed as objective function and design constraints, the optimum design of the cantilever retaining wall has been investigated via HSA [33]. According to the extensive research results in the literature, no study has been found in which the optimum values for the number of runs and the number of maximum iterations with optimum HSA control parameters have been investigated based on the Taguchi method with different engineering problems.…”
Section: Introductionmentioning
confidence: 99%